Mechanical Behaviors of Methane Hydrate-Bearing Sediments Using Montmorillonite Clay. (February 2019) - Wang, Lei; Liu, Weiguo; Li, Yanghui; Wu, Peng; Shen, Shi
Abstract: In this study, we compared the shallow marine soil of Shenhu area in the north of the South China Sea with Montmorillonite Clay and found that there were significant similarities between them, including special gravity, median diameter and proportion of different components of soil, so we utilize the Montmorillonite Clay to take the place of the shallow marine soil of the South China Sea to study its mechanical properties. A series of triaxial tests were conducted and the results indicated that (1) the sediment's failure strength increases with the decreases of temperature. (2) The maximum deviator stress increases with the confining pressure. (3) The sediment's strength increases with the decreases of porosity. (4) The change of the failure strength is mainly affected by the cohesion force, and the cohesion force increases with the decrease of the temperature.